Comparison and evaluation of the Telehealth systems using a discrete event simulation - Griscenko, Natalia (Cranfield University, 2012)
The telehealth is the delivery of health-related services at a distance using communication technologies. The telehealth provides important benefits: allows to provide the access to the healthcare service reducing need for a physical stay and decreasing the healthcare cost. This industry’s popularity and the importance constantly increases because of the number of rapid increase of the population share a ected by the chronic diseases. However, the telehealth service development requires substantial investment of finances, time and substantial expertise. A method of comparison and evaluation of the current telehealth systems helps to create the telehealth service while minimising an amount of the resources wasted. The method to simulate, evaluate, and compare the telehealth systems have been created through the review of the state-of-the-art techniques of evaluation and comparison of the existing telehealth systems. Then, it was applied to several the real life telehealth systems. The outcome of this work is (i) the method to construct Discrete Event Simulation (DES) models of the telehealth systems, (ii) twelve the DES models of the current telehealth systems, (iii) the list of suggestions for the future research to increase the quality of the DES models, (iv) the method to choose parameters and to develop metrics to evaluate the telehealth systems, (v) the method to define an approach to compare the telehealth systems, (vi) the evaluation and comparison results of twelve the current telehealth systems. The bottom line of the current research is that the simulation is an e ective way to evaluate and compare the telehealth systems. The DES approach is a viable way of gaining an insight into the telehealth systems properties, although it requires a substantial amount of the future research to mature the method to evaluate and compare the telehealth systems.